Restarting living donor kidney transplant during COVID-19: a single center experience - Zahran, Mochammad Fairuz (Sanglah General Hospital, 2022)
Background: The decision to declare COVID-19 a pandemic in March 2020 turned the situation into a medical emergency that also affected the care and program for kidney transplants. Since it enhances patients’ quality of life, kidney transplantation has been the only effective therapy option for people with end-stage renal disease (ESRD). While kidney transplants are extremely beneficial, there is still a significant risk of COVID-19 infection, particularly for recipients who must take immunosuppressive medications following the procedure. Purpose: This study aimed to evaluate kidney transplant procedures in Dr. Sardjito General Hospital before and during the pandemic based on recipients’ and donors’ characteristics and laboratory findings such as creatinine and urine time. Patients and methods: This study is designed as cross-sectional analytic research to evaluate 30 patients who underwent kidney transplants in Dr. Sardjito General Hospital before (April 2019-2020) and during (April 2020-2021) the COVID-19 era. Data analyses were carried out using SPSS version 25.0 and were served with simple charts and tables. Results: There was a decrement in kidney transplant procedures before (n=16) and during (n=14) COVID-19. The recipients that underwent the most transplantation before the pandemic were 20-29 years old, while during the pandemic were 40-49 years old. There is no significant difference in length-of-stay before (12.0±4.17 days) and during (9.29±3.73 days) COVID-19 (p=0,077). Laboratory findings such as creatinine of pre-transplantation (9.47±4.05; 7.81±6.00) and 3 months post-transplantation (1,55±0,78; 1,15±0,67) also did not show significant changes (p=0,153) as well as urine time (245.60±225.55; 428.38±657.70; p=0.321). Conclusion: In the COVID-19 era and prior, kidney transplant procedures declined at Dr. Sardjito General Hospital. There are no significant variations in duration of stay, creatinine levels before and three months after transplantation, or urine frequency. Overall, transplant results were comparable before and after the COVID-19 era.